On the problem of impact interaction of a solid and a liquid with free surface under flow separation - Polyakov, N. V.; Goman, O. G.; Katan, V. A. (Reports of the National Academy of Sciences of Ukraine, 2016)
A general method of solution to the mixed problems of hydrodynamic impact with the inertial flow separation of a liquid in a two-dimensional model with the use of the apparatus of singular integrals in sense of the Hadamard finite part is introduced.